The Salience and Pervasiveness of the Literary Figure of the Jew in Latin America: From Sor Juana Inés de la Cruz to Jorge Luis Borges. - Wassner, Dalia (Latin American Research Review, 2019)
Jews of Latin America, from the colonial period to the present, have been branded heretical, inauthentic, or treasonous and perceived as threats to the colonial domination of Spainâ€™s Counter-Reformation and modern iterations of nationalism in the region. Sor Juana InÃ©s de la Cruzâ€™s El divino Narciso (1689) and Jorge Luis Borgesâ€™s â€œEl milagro secretoâ€ ([1944] 1993) indicate the salience and pervasiveness of the figure of the Jew, experientially and conceptually, in the regionâ€™s literary conversations about power, collectivity, and legitimacy vis-Ã -vis colonial and modern Europe. The two works reflect a transatlantic, multigenerational, and multigendered conversation that approaches the elimination of the Jew as a bargain that involved a simultaneous loss of American agency on a world stage. Sor Juana emerges not only as Latin Americaâ€™s first female intellectual; she is Borgesâ€™s precursor in demanding an American regional identity and global agency apropos of the metropoleâ€™s exclusionary violence toward the Jew within.